Pregunta
upstudy study bank question image url

(1) The equation of two diameters of the circle passing Brough the point \( (3,4) \) are \( x+y=14 \) and \( 2 x-y=4 \) Find the equation of the circle

Ask by Hammond Riley. in Nepal
Feb 06,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The equation of the circle is \( (x - 6)^2 + (y - 8)^2 = 25 \).

Solución

To find the equation of the circle, follow these steps: 1. **Determine the Center of the Circle:** The two given diameters of the circle are: \[ x + y = 14 \quad \text{(Diameter 1)} \] \[ 2x - y = 4 \quad \text{(Diameter 2)} \] The center of the circle is the intersection point of these two diameters. Solve the system of equations to find the center \((h, k)\): \[ \begin{cases} x + y = 14 \\ 2x - y = 4 \end{cases} \] **Adding the two equations:** \[ (x + y) + (2x - y) = 14 + 4 \\ 3x = 18 \\ x = 6 \] **Substitute \(x = 6\) into the first equation:** \[ 6 + y = 14 \\ y = 8 \] So, the center of the circle is at \((6, 8)\). 2. **Find the Radius of the Circle:** The circle passes through the point \((3, 4)\). Use the distance formula to find the radius \(r\): \[ r = \sqrt{(3 - 6)^2 + (4 - 8)^2} \\ r = \sqrt{(-3)^2 + (-4)^2} \\ r = \sqrt{9 + 16} \\ r = \sqrt{25} \\ r = 5 \] 3. **Write the Equation of the Circle:** The standard form of the equation of a circle with center \((h, k)\) and radius \(r\) is: \[ (x - h)^2 + (y - k)^2 = r^2 \] Substituting the values we found: \[ (x - 6)^2 + (y - 8)^2 = 5^2 \\ (x - 6)^2 + (y - 8)^2 = 25 \] **Alternatively**, expanding the equation: \[ x^2 - 12x + 36 + y^2 - 16y + 64 = 25 \\ x^2 + y^2 - 12x - 16y + 100 = 25 \\ x^2 + y^2 - 12x - 16y + 75 = 0 \] **Final Answer:** The equation of the circle is \[ (x - 6)^2 + (y - 8)^2 = 25. \]

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Beyond the Answer

To find the equation of the circle, we first need to determine its center, which is the intersection point of the two diameters. Let's solve the equations: From \( x + y = 14 \): \[ y = 14 - x \] Now substitute this expression for \( y \) into the second equation \( 2x - y = 4 \): \[ 2x - (14 - x) = 4 \] \[ 2x - 14 + x = 4 \] \[ 3x - 14 = 4 \] \[ 3x = 18 \] \[ x = 6 \] Now substitute \( x = 6 \) back into the first equation to find \( y \): \[ 6 + y = 14 \] \[ y = 8 \] So, the center of the circle is at \( (6, 8) \). Next, we need to find the radius. Since the point \( (3, 4) \) lies on the circumference, we can use the distance formula to find the radius: \[ r = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} = \sqrt{(6 - 3)^2 + (8 - 4)^2} = \sqrt{3^2 + 4^2} = \sqrt{9 + 16} = \sqrt{25} = 5 \] Now we can express the equation of the circle in standard form: \[ (x - 6)^2 + (y - 8)^2 = 5^2 \] Thus, the final equation of the circle is: \[ (x - 6)^2 + (y - 8)^2 = 25 \]

Latest Geometry Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad